2021
DOI: 10.3390/ijerph18041501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Child Maltreatment: Income Instability and Parenting Issues

Abstract: Introduction: Children are widely recognized as a vulnerable population during disasters and emergencies. The COVID-19 pandemic, like a natural disaster, brought uncertainties and instability to the economic development of the society and social distancing, which might lead to child maltreatment. This study aims to investigate whether job loss, income reduction and parenting affect child maltreatment. Methods: We conducted a cross-sectional online survey of 600 randomly sampled parents aged 18 years or older w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 28 publications
2
59
0
3
Order By: Relevance
“… Wong et al (2021) reported that having difficulty discussing COVID-19 with children was significantly associated with more physical abuse, whereas having more confidence in handling preventive COVID-19 attitudes with children was negatively associated with physical punishment and very severe physical assaults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Wong et al (2021) reported that having difficulty discussing COVID-19 with children was significantly associated with more physical abuse, whereas having more confidence in handling preventive COVID-19 attitudes with children was negatively associated with physical punishment and very severe physical assaults.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that income reduction or job loss was significantly associated with severe physical assaults towards children. Nevertheless, income reduction and job loss were significantly associated with less psychological aggression ( Wong et al, 2021 ). On the other hand, Lawson et al (2021) reported that parents who lost their jobs were more likely to psychologically maltreat their children during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Poverty has been shown to be significantly related to child maltreatment and the relationship is still strong (Berger and Waldfogel, 2011;Drake and Jonson-Reid, 2013;Pelton, 2015;Yang, 2015). The COVID-19 outbreak acts as a catalyst for a considerable rise in child maltreatment by exacerbating household poverty, and studies have shown that unemployment during the epidemic, family income instability and consequent poverty are the important risk factors for child maltreatment (Lawson et al, 2020;Lee et al, 2021;Wong et al, 2021). In 2020, the widespread economic downturn and income decrease pushed more disadvantaged families under greater financial and parenting pressure.…”
Section: Risk Factors Of Child Maltreatmentmentioning
confidence: 99%
“…Di samping itu, program stay at home selama pandemik kerap diikuti timbulnya sikap agresif anak yang menyebabkan peningkatan status stress pada orang tua. Sehingga orang tua cenderung menggunakan kekerasan kepada anak saat di rumah (Berkel et al, 2020;Chung et al, 2020;Wong et al, 2021). Di samping itu, kebanyakan orang tua yang penggangguran di suatu wilayah tertentu akan meninggalkan anak-anak mereka untuk bekerja di luar kota.…”
Section: Dukungan Emosional Orang Tuaunclassified